العلاقات الجزائرية_التركية : بين الإرث التاريخي والتحديات الراهنة - رزايقية, حنان (جامعة الوادي University of Eloued, 2017)
الغرض من هذه الورقة هو دراسة العلاقات الجزائرية- التركية من خلال الإشارة إلى عدد من الجوانب التي تؤكد هذه العلاقات: أولا: أن طبيعة العلاقات التي تم تطويرها بين الجزائر والإمبراطورية العثمانية كانت إحدى أهم المراحل في التاريخ الجزائري . ثانياً: أن هذه الورقة تحاول أيضا أن تلقي الضوء على طبيعة العلاقات بين البلدين خلال الاستعمار الفرنسي للجزائر. حيث كانت العلاقات بين البلدين منعدمة تقريبا، هذه الأخيرة التي كان موقفها غير واضح تجاه الاحتلال الفرنسي. ثالثا: البحث في العلاقات الجزائرية- التركية في الفترة الراهنة. The purpose of this paper is to study the Algerian-Turkish relationships with special reference to a number of aspects that underline such relationships: Firstly, the nature of relationships that were developed between Algeria and the Ottoman Empire have marked one of the most important era in Algeria’s history; Secondly, the paper will also try to throw the light on the nature of relationships between the two countries during the French colonization of Algeria; relations between the two countries were almost inexistent and the Ottoman Empire hardly expressed its stand with regard to French colonial policies in Algeria. Thirdly Search Algerian-Turkish relations in the current period
Keywords: العلاقات الجزائرية التركية